Abnormalities in rich-club connections are associated with an exacerbation of genetic susceptibility to schizophrenia - Yang Li; Eryi Sun; Rao Dai; Jian Chen; Haixia Huang; Xiuhong Shan; Yuefeng Li (BMC Psychiatry)
Abstract Background Schizophrenia (SZ) is a highly heritable and heterogeneous disorder that is often associated with widespread structural brain abnormalities. However, the causes of interindividual differences in genetic susceptibility remain largely unknown. This study attempted to address this important issue by utilizing a prospective study in which unaffected first-degree relatives of SZ (FH+) were recruited. Methods A total of 198 participants (143 FH + and 55 healthy control participants) were recruited and completed diffusion tensor imaging scans, graph theory analysis and semiannual standardized clinical evaluations within the first three years. Results FH + participants who developed SZ (SZ/FH+) had similar but pronounced structural network changes at baseline compared to FH + participants who did not (HC/FH+). Additionally, among network properties, rich-club connections showed a good correlation with the severity of SZ, which was the most significant and stable effect. Logistic regression analyses showed that rich-club connections at baseline had high predictive accuracy for the subsequent occurrence of SZ. Conclusions Among healthy people with a familial history of SZ, those who exhibit decreased rich-club connections are susceptible to developing this disease. Our findings may aid in the development of timely interventions to prevent SZ and possibly assist researchers and clinicians in evaluating the efficacy of interventions.